2020
DOI: 10.1155/2020/8239474
|View full text |Cite
|
Sign up to set email alerts
|

Association between Chronic Pain and Diabetes/Prediabetes: A Population-Based Cross-Sectional Survey in Saudi Arabia

Abstract: Background. Diabetes is a debilitating chronic health condition that is associated with certain pain syndromes. The present study sought to evaluate chronic pain and its association with diabetes mellitus at a population level. Methods. A population-based cross-sectional questionnaire survey study was conducted in Al-Kharj, Saudi Arabia, from January 2016 to June 2016. Participants from both private and governmental institutions were selected following a multistage sampling technique and using a cluster sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
2
7
0
1
Order By: Relevance
“…Nevertheless, our findings have shown that compared to those with NGM, the association of increasing TV time with the severity of bodily pain at any given time point is more pronounced in those with T2D than with prediabetes. These observations support the evidence that people with T2D, especially those with long-standing cases, are predisposed to heightened pain due to systemic inflammatory response and vascular complications associated with peripheral neuropathy in T2D [26,27]. Moreover, compared to those without T2D, people with T2D tend to spend more time in sedentary behaviour [29].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Nevertheless, our findings have shown that compared to those with NGM, the association of increasing TV time with the severity of bodily pain at any given time point is more pronounced in those with T2D than with prediabetes. These observations support the evidence that people with T2D, especially those with long-standing cases, are predisposed to heightened pain due to systemic inflammatory response and vascular complications associated with peripheral neuropathy in T2D [26,27]. Moreover, compared to those without T2D, people with T2D tend to spend more time in sedentary behaviour [29].…”
Section: Discussionsupporting
confidence: 83%
“…For example, a review of experimental and intervention-trial evidence has shown that reducing sedentary behaviour can beneficially impact cardiometabolic and inflammatory biomarkers associated with T2D [25]. Also, T2D has been shown to be associated with heightened chronic pain conditions, especially neuropathic pain [26][27][28]. Since studies have also shown that sedentary time is more pronounced in those with T2D compared to those without [29], there is a need to better understand the convergence of high sedentary time with T2D on trajectories of bodily pain.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of muscle strength, particularly in the legs, in patients with type 2 diabetes could be one of the important contributing factors in developing chronic lower back pain, as lack of support leads to constant wear and tear due to extra load on the intervertebral disc [ 38 ]. Therefore, musculoskeletal pain management is of great significance in the lifestyle intervention of type 2 diabetes [ 39 ].…”
Section: Reviewmentioning
confidence: 99%
“…[38][39][40][41] Since many patients take non-BZ hypnotics ("Z-drugs") concurrently or alternating with BZs, [42] and these people may be taking medications for pain-associated sleep disturbances, [43,44] where chronic non-neuropathic pain has been found to be associated with diabetes, this can introduce confounding. [45] As Z-drugs have previously been observed to increase diabetes risk in people with non-apnea sleep disorders, [42] this study only included patients taking 1 type of benzodiazepine in the past month to avoid confounding.…”
Section: Discussionmentioning
confidence: 99%